Early Patient Satisfaction Results on a Modern Generation Fixed-Bearing Total Ankle Arthroplasty. (September 2016) - Oliver, Shelley M.; Coetzee, J. Chris; Nilsson, Lawrence J.; Samuelson, Kathryn M.; Stone, Rebecca M.; Fritz, Jacquelyn E.; Giveans, M. Russell
Background: This study presents patient-reported outcomes and patient satisfaction data for the largest series of US patients undergoing modern fixed-bearing total ankle arthroplasty (TAA). Methods: We retrospectively reviewed the records of 300 consecutive patients who underwent 321 modern, fixed-bearing TAAs at a single institution. Veterans Rand 12-Item Health Survey (VR-12), Ankle Osteoarthritis Scale (AOS), and the American Orthopaedic Foot & Ankle Society (AOFAS) Hindfoot score were collected preoperatively and at subsequent follow-up appointments. A patient satisfaction survey was also distributed to each patient postoperatively. Of the 321 TAAs, 245 (232 patients) had a minimum of 2-year follow-up and a complete data set. Furthermore, 192 patients underwent concomitant procedures. The average follow-up was 38.9 months (24-84.5). Eight patients have been lost to follow-up (7 deceased and 1 refused further follow-up). Results: The mean AOFAS score preoperatively was 41.1 and at latest follow-up was 84.6 ( P < .01). The mean VR-12 score was 29.7 (Physical) and 54.1 (Mental) preoperatively and 42.7 (Physical) and 55.7 (Mental) at latest follow-up ( P < .01 and P > .05, respectively). AOS pain and disability scores improved significantly after TAA ( P < .01). The patient satisfaction survey indicated that 84% experienced very good to excellent pain relief, 78% reported improved ability to perform daily tasks, and 54% indicated improvement in their ability to perform heavy work or recreational activities. In addition, 94% would probably or definitely have the procedure on the contralateral ankle. Two patients underwent revision TAA at a minimum of 36 months; 8 patients failed the primary TAA and were converted to ankle fusions at a mean of 20.1 months (6.1-46.1). Conclusion: Early results of a large series of a modern TAA system demonstrate improvement in patient satisfaction, quality of life, activity, and pain for patients with end-stage ankle arthritis. Early revision was due to infection or loosening of the tibial component. Level of Evidence: Level IV, case series.